Sustainable Economic Growth: An Empirical Study for the Asia-Pacific Economic Cooperation Forum - Dávalos, José (International Journal of Energy Economics and Policy, 2016)
This study analyses the validity of environmental Kuznets curve (EKC) hypothesis for the Asia-Pacific Economic Cooperation Forum (APEC), within the period 1992-2012. Three econometric models are performed, which use different environmental quality indicators as dependent variable. Model 1) uses CO2 total emissions in APEC, model 2) uses CO2 emissions generated from coal consumption, and model 3) uses CO2 emissions generate from petroleum consumption. Pedroni and Kao cointegration approach are applied for testing long-run relationship between variables for each model. Fully modified ordinary least squares (FMOLS) method is employed for determining the elasticities of the long-run relationships. The analysis finds that an EKC is held under model 1, and 3, but for model 2 the relation between the variables does not show an inverted U shape behavior. Additionally descriptive analysis and model 2 suggest that coal consumption has been increasing in last years, because of the effect in CO2 emissions; even more in this specific indicator, economic activity is leading to an unsustainable growth scenario in APEC. Keywords: Environmental Kuznets curve, CO2 emissions, economic growth. JEL Classifications: Q5, Q56